Material balance and ability of beach nourishment for the northern coast of Cai river mouth in Nha Trang bay - Long, Bui Hong; Cong, Nguyen Chi; Binh, Tran Van (Vietnam Journal of Marine Science and Technology, 2019)
Nha Trang bay is considered one of the 29 most beautiful bays in the world. This is a coastal area with potential for tourism development with many beautiful clean beaches and dozens of large and small islands. In 2016, Nha Trang has attracted 5 million tourists including 1.2 million international tourists. Recently, while the development of tourism in the country tends to slow down, Nha Trang tourism in the period 2011–2016 increased by 19%/year on average. According to the statistics of Khanh Hoa province, Nha Trang tourism occupies 99% of the province. The number of hotels located in the immediate vicinity of Nha Trang’s central beach is 98% within 500 m from the coastline. In order to develop sustainable tourism, in addition to good management and protection of coastal and estuarine beach environments, more attention should be paid to the rehabilitation, expansion and development of the beach in the northern and southern areas to relieve pressure on the central beach and expand the investment potential and tourism development of Nha Trang city. According to survey data and the calculations based on a local project between Institute of Oceanography and Khanh Hoa province: "Identifying areas capable of rehabilitating and developing artificial beach and proposing solution for protection of natural beaches in Nha Trang Bay" (2014–2016), three beach nourishment scenarios have been simulated and evaluated, suggesting a number of potential areas for rehabilitation and artificial nourishment for the western coast of Nha Trang bay.